Biyo İktidar ‘gözetim’inde Planlama: Tarlabaşı Kentsel Dönüşüm Örneği - Hayal, Seda (Fen Bilimleri Enstitüsü, 2013)
Biyo iktidar, kapitalizmle çok iyi çalışan bir iktidar tekniğidir ve bedenleri disipline eden; nüfusları düzenleyen iktidar tekniklerinden daha üst bir yerde konumlanıp her iki tekniği de içinde barındırır. Günümüz iktidar tekniği olarak adlandırabileceğimiz biyo iktidar her zaman ve her yerdedir. Kavramı, üç başlık altında incelemek mümkündür: Nüfus düzenleme, norm/normalizasyon toplumu ve gözetim/gözetleme toplumu oluşturma. İnsanları biyolojik bir tür olarak gören bu iktidar tekniği ile planlamanın ilişkisinin kurulması, yine biyo iktidarın üç bileşeni üzerinden kurgulanmaya çalışılmıştır. Kent planlamanın pek çok alanda kavramsal olduğu kadar; uygulama anlamında da biyo iktidarla kesiştiğinden söz etmek mümkündür. Planlama, nüfus hareketlerini yönlendirici özellikleri ile insanları yığınlar halinde hareket ettirebileceği gibi; üst ölçekten gelen kararlarla doğrudan kent mekanını etkileyebilecek bir araç olabilecektir. Türkiye gibi gelişmekte olan ülkelerde geç gelen sanayileşmeyle birlikte başlayan göç hareketleri ve gecekondulaşmayla ortaya çıkan çarpık kentleşmenin sonucu olarak, günümüzde gittikçe popülerleşen kentsel dönüşümle ‘planlama’ yapılmaya çalışılmaktadır. Bu bağlamda yaşanan planlama süreçlerinin de doğrudan biyo iktidarla ilişkisinin ortaya konmasının anlamlı olduğundan bahsedilebilecektir. Gerek kent planlama süreçleri; gerek kentsel dönüşüm konusu özelinde, yaratılmaya çalışan norm/normalizasyon toplumunun izlerine rastlamak söz konusudur. Kentsel ayrışma, sosyal ve fiziksel olarak ayrışma olarak değerlendirildiğinde, bu süreçlerin bazen planlama ile başladığından; kimi zaman da planlama sebebi olarak gösterilecek başlıklar olduğundan bahsetmek mümkündür. Dışlanma ya da kent mekanının eşit kullanılamaması gibi konular, toplumda yer alan dezavantajlı olarak adlandırabileceğimiz grupların yaşadığı mağduriyetin konusudur. Bu topluluklar ya da bireyler normalizasyon toplumunun dışında kalmamak için çabalamak durumundadırlar. Dışlanmamak için ya kimliklerini saklamak ya da ‘normal’ bir hayata geçmek zorunda kalmaktadırlar. Gözetim/Gözetleme toplumunun yaratım sürecinde ise, Panopticon hapishane modelinin yaratılmak istenen toplum modeline dair söz söylediğinden bahseden Foucault’dan hareketle, kent mekanı değerlendirilmeye çalışılmıştır. Kentlerin gözetimi, gerek kamu kuruluşları; gerekse özel sektör tarafından kullanılan kameralandırma sistemiyle sağlanmaktadır. Bunun dışında gözetleme ile sağlanan bilginin kentlerde yarattığı iktidar, planlamaya girdi sağlamaktadır. Bilginin nesnesi olan insanlar kimi zaman gözetlenme duygusuyla kendi kendini denetlemek ve normalizasyon toplumuna katılmak zorunda kalmaktadır. Bu noktada, gözetleme ve normalizasyon toplumunun birbirleri ile olan yakın ilişkisine dikkat çekmek yerinde olacaktır. Kent mekanının günümüz normlarına göre boş zamanlarda gidilmesi gereken alışveriş merkezleri, çalışılması gereken iş kuleleri, yaşanması gereken güvenlikli kapalı siteler vb. alanlarda hem normalizasyon toplumu oluşturularak insan yığını düzenlenmektedir; hem de tüm bu mekanlarda bireyler gözetlenerek disipline edilmektedir. Kentsel dönüşüm özelinde konu ele alınırken de, aslında planlama ve biyo iktidarın bağı konusunda tespiti yapılan birçok kalemden bahsedilebilecektir. Nüfus düzenleme konusunda kitlesel göçler, zorunlu göçler ile başlayan insan yığını hareketlerinin; yerinden etmelerle tekrara düştüğünden bahsedebiliriz. Bunun dışında kentsel dönüşümle yerinden edilenler için biçilen TOKİ evlerinin, yaratılmak istenen normalizasyon toplumu açısından ele alınması da anlamlı olmaktadır. Bir diğer açıdan baktığımızda, kentsel dönüşümle kentsel ayrışmanın çok daha üst perdelere çıktığından bahsetmek mümkün olacaktır. Bu noktada rant elde edilen kent merkezlerinde, bir insan türünün bir diğer insan türüne tercih edilmesi söz konusudur. Kentsel dönüşüm öncesinde, alanda yapılan araştırmalarla alanın kullanıcılarının bilginin nesnesi haline geldiğine dair değerlendirme yapmak mümkündür. Bunun dışında, kentsel dönüşüm sonrasında yeni oluşturulan mekanların ise yine günümüz normlarına uygun ve kameralı sistemlerle inşa edilmesinden de gözetim toplumunun yaratımı olarak bahsedilebilecektir. Tarlabaşı Kentsel Dönüşümü’nün konu bağlamında ele alınması, alanın kent merkezinde olması; tarihi ve özel bir dokuya sahip olması açısından önemlidir. Dönüşüm süreci öncesi ve sonrası olarak iki dönemde biyo iktidarla ilişki kurulabilecektir. Bu bağlamda, dönüşümün asıl sebeplerinin başında rant adını görmek şaşırtıcı olmayacaktır. Bunun yanı sıra alanın kullanıcıları ‘normalizasyon toplumuna’ uygun değillerdir. Mahallede devamlı devriye gezen polis arabaları ve Tarlabaşı Bulvarı üzerinde konumlanan Emniyet Müdürlüğü’nün varlığı ve dönüşüm sürecinin başlatılmasından evvel alanda yapılan araştırmalarla edinilen bilgilerin Panopticon olarak görülebilecek unsurlar olduğundan bahsedilebilecektir. Nüfus düzenleme adına yasal dayanakların üretilmesi; Tarlabaşı yasası olarak da bilinen 5366 sayılı yasanın çıkarılması, buradaki insan yığınını ve tarihi dokuyu istediği gibi şekillendirebilecek araçlara sahip bir planlama iktidarının anlayışıdır. Dönüşümden sonra elde edilecek olan alan biyo iktidar çerçevesinde değerlendirildiğinde; proje alanının kullanıcıları tamamen değişecektir. Süreç, yönetim eliyle gerçekleştirilen mutenalaştırma olarak da okunabilecektir: Alanda sosyal bir dönüşüm gerçekleşecektir. Diğer bir önemli nokta; alanın tarihi, koruma altında olan dokusu özelliğini kaybedecek ve fonksiyonel olarak da günümüz ‘normal’ini yansıtacak olan butik oteller, alışveriş merkezleri, ofis alanları, rezidanslar olarak kendini gösterecektir. Ayrıca, tüm bu yeni alanlarda kameralı bir gözetleme sistemi yer alacaktır. Genel olarak fiziki dokusundan sosyal yapısına kadar alanda ciddi bir değişim olacaktır. Ortaya konan bu ilişki ağı sonucunda, iktidar ile kendi yarattığı direniş mekanizmalarının ilişkisi önemli olacaktır. Kentsel müdahalelerde, toplumsal farkındalık ve hak talebi önem taşımaktadır. Bu çerçevede, toplumun kentsel muhalefet algısı taşımasına ihtiyaç duyulmaktayken; kent planlamanın en önemli direniş mekanizmaları olarak da iki kavram öne çıkmaktadır: Kamu yararı ve planlamada katılım. Bu iki ana eksende kent planlama değerlendirildiğinde, her alanın biricikliği ve korunması gereken değerlerine karşı hassas bir yaklaşım; kentsel dönüşüm değerlendirildiğinde ise, alanının kullanıcılarının katılımı ile gerçekleştirilen ‘yerinde dönüşüm’ kavramının ele alınmasının gerekliliği ortaya çıkmaktadır. Biyo iktidarın biyolojik bir tür olarak gördüğü insanların, kent mekanındaki ‘değer’inin planlama açısından bir girdi olması gerekmektedir. Kentler, insanlar için ve insanlarla vardır; insanı sosyal etkileşimleri olan, kültürleri oluşturan ve fiziki çevrede ‘yaşayan’ varlıklar olarak kabul eden planlama anlayışıyla şekillendirilmelidir.

Bio-power is a power concept that works very well with capitalism and it sits in a higher place then the power concepts that disciplines bodies and regulates the populations while hosting both concepts within it. We can name bio-power as today s concept of power and it is everywhere all the time. The concept can be analyzed under three headings: Population regulation, norms/normalizing society and monitoring/surveillance society creation. Population regulation perceives the communities as mass of humans. Bio power tries to regulate the population to be able to make use of people for capitalism as well as strengthening its own authority. Norm/normalizing society consists of norms which are used for regulating relations in the society. Norms can be used both to regulate the population and to discipline the body. Most of the institutions help creating the norms such as family, school, military etc. People are forced to be normalized otherwise they would be excluded from the social life. Monitoring/surveillance society comes from the idea of Panopticon. Panopticon is an architectural form that could be used as prison but in fact it reflects the idea of surveillance which serves to the power. In the center there is an inspection tower which the person in the cell doesn’t know when he/she is watched. That makes the person to be his/her own police. The idea of being watched regulates the individuals’ attitudes. This concept also means to be informed about the person in the cell. The knowledge again helps the power to strengthen. The relationship between this concept of power, which sees humans as solely a biological species and planning is constructed out of the three components of bio-power. It is possible to say that urban planning intersects with bio-power in many areas such as concept as well as in terms of its application. Planning can be a tool that can directly affect urban space with the help of the upper scale decisions as well as moving masses within movements of the population. Starting with the late industrialization in developing countries such as Turkey, migration movements and an increasing number of shantytowns, which was a result of unplanned urbanization, made ‘planning’ and urban transformation increasingly popular today. The direct relationship between bio-power and planning processes in this context will be discussed. It is possible to come across the signs of a society that was attempted to be created by norms/normalization in both urban planning processes and in the subject of urban transformation. When the urban decomposition is seen as the decomposition of the social and physical in all, it is possible to talk about these processes as subjects that start with planning and sometimes as reasons for planning. Subjects such as not being able to use the urban space equally or marginalisation are the signs of victimization experienced by the disadvantaged groups in society. These communities or individuals are obliged to strive to avoid being outsiders of the normalizing society. In order not to be excluded they usually either have to hide their identity or are forced to adapt to a ‘normal’ life. In the creation of a Monitoring/Surveillance society, urban space is being assessed through Foucault’s theory about the Panopticon prison model having an influence on the process of creating this society. Supervision of the cities is achieved by surveillance systems sometimes provided by the public institutions and sometimes by the private sector. Other than that, the power created by the information provided through the monitoring of cities provides input for planning. As people become objects of knowledge, they are forced to participate in society with a sense of self-control and normalization created by the sense of being watched. At this point, it would be appropriate to mention the close relationship between surveillance and the normalization of societies. Urban spaces are filled with shopping malls to spend free time in, business towers to work in and protected living areas to live in according to todays norms as the normalization of the society is created by organising human masses while individuals are being watched and disciplined in the meanwhile. When dealing with the case of urban renewal, a lot of areas where there is a bond between planning and bio-power will be mentioned. We can talk about the way in which the mass and forced migrations being replaced and repeated by recent displacements in order to move masses of people. It will also be meaningful to look at the TOKI houses from the angle of a normalizing society’s point of view as they are created for the displaced people as a result of urban transformation. When we look at it from another point of view, it will be possible to talk about the fact that the urban transformation and urban segregation has hit an all time high. At this point it is obvious that some kinds of people are preferred over others in city centres that bring income. It is possible to come to a conclusion that the inhabitants of the specific area become the object of knowledge prior to the urban renewal. Again, it will be possible to regard the newly built areas of post urban renewal as the creation of a surveillance society with their way of conforming to today’s norms as well as their systems of surveillance. The fact that Tarlabaşı is situated in the center of the city as well as having a special and historical presence is important to the subject of urban renewal. A connection will be made with the bio-power in both periods of pre and post urban renewal processes. In this context it would not be surprising to find out that financial gain is one of the most important reasons for the renewal. In the meanwhile the habitants aren’t suitable for the ‘normalization society’. The constant police presence with the police cars and the Police Department, which is situated in the Tarlabaşı Bulvarı as well as the research done before the renewal process will provide a basis to liken this to the Panopticon. The creation of the legal instruments in order to produce regulation of the population; the Law No. 5366, also known as the law of Tarlabaşı, is a result of the government with the power of a planning approach that has the tools to shape the historical presence and the inhabitants as it wishes. The assessment of the area that will be created after the renewal within the bio-power reference is the habitants, users of the project area will change completely, and the process can be read as gentrification carried out by the government. There will be a social regeneration in the area. An other important point is that the historic preservation area will loose its unique features while reflecting today’s ‘normal’ by accommodating boutique hotels, shopping centres, offices and residences. Besides, all these new areas will be fitted with camera surveillance systems. There will be a serious change from physical pattern to social structure. This renewal process also can be analyzed both from inside and outside of the project area. When we evaluate the outside look to the project area we will be dealing with the municipality and the construction company’s aim to demonstrate the area as a poisoned patient. They try to show the area like an unsafe, ugly, rubbish place and that it is their mission to change the dynamic to a ‘beautiful place’ like it was in the history by the help of the law no 5366. When we evaluate the reflection of the process in the project area from the inside, we will find out that the inhabitants think that the renewal happens because of their existence in the center of the city and they agree that the area will be a ‘beautiful’ place as the authority says. This let us see how the normalization society is created and convince the people even if they are the aggrieved side of the project. As a result of the bond between these networks, the relationship between power and resistance mechanisms it creates itself will be important. Public awareness, and the demand for rights carry a weight with the urban interventions. In this point of view, the community has to have the perception of urban struggle while two of the most important concepts that help create resistance mechanisms of urban planning seem to be: public interest and participation in the planning. Within these two mechanisms what becomes apparent is the necessity of the importance being placed on the idea of a sensitive approach to preservation of the uniqueness of each area when urban planning is evaluated, as well as ‘on-site renewal’ with the participation of the habitants of the area when urban renewal is evaluated. Instead of seeing humans as biological species, the value of the people in the urban space should be an input for urban planning. Cities, which are born for people and exist with people, should be formed according to a planning mentality that accepts humans as social creatures.
Urban Planning Under The Biopower Surveillance: Tarlabaşi Urban Renewal
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2013
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2013
Keywords: Biyo iktidar; Foucault; Şehir Planlama; Kentsel Dönüşüm; Tarlabaşı; Bio Power; Foucault; Urban Planning; Urban Renewal; Tarlabaşı